Restorative Justice at the Grassroots: Exploring Cultural Integration and Police Facilitation in Criminal Case Settlements in Waesala, Indonesia - Rahawarin, Fauzia; Wattimena, Husin; Muhammad Fadhil; Sahur Ramsay; La Ode Aindo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines the effectiveness of Restorative Justice (RJ) implementation in resolving criminal cases in the jurisdiction of Waesala Police, West Seram Regency, Maluku Province. The study used a Mixed Methods Sequential Explanatory Design approach, combining quantitative analysis based on Structural Equation Modeling (SEM) and qualitative analysis through in-depth interviews and thematic coding with NVivo 12 Plus. The quantitative stage focuses on dimensions such as Police Socialization (SP), Victim Involvement (KK), Process Effectiveness (EP), and Satisfaction and Sense of Justice (KRK). The results of the CFA test showed high validity and reliability of the measurement model, with the dimensions of Empathy (EP) and Cultural Restorative Justice (KRK) as dominant contributors based on a factor loading value of 0.97. Qualitative findings revealed important themes such as barriers to victim education, the role of the police as a facilitator, perceptions of justice, and case criteria that are eligible for RJ. Data triangulation ensured depth of context and theoretical confirmation. The results of the study prove that RJ not only increases procedural satisfaction and social harmony, but is also in line with local cultural values ​​when facilitated properly. This study provides academic contributions as well as practical recommendations for law enforcement institutions in designing RJ policies that are relevant to local conditions.